(untitled) (SAARC Journal of Agriculture, 2023)
This study examines the influence of COVID-19 pandemic on livestock sectors in Sudur Paschim Province (far western province) of Nepal with a focus on the government’s response. Analyzing provincial interventions in the livestock sector, we present findings from a primary survey and interviews with livestock farmers, agri-business traders, market agents, and key stakeholders across Kanchanpur, Kailali, Doti, and Achham districts. These districts represent the diverse agro-climatic conditions of far western Nepal. Using mixed methods, we combine qualitative and quantitative data to analyze the impact on livelihoods, business performances, employment, and income for livestock farmers and traders compared to the pre-pandemic scenario of 2019. The pandemic significantly disrupted the livestock and fresh meat production system due to supply chain disruptions, affecting all stakeholders – farmers, producers, suppliers, traders, agro-businesses, and consumers. The repercussions varied among these actors. Dairy farmers experienced a 50-60 percentage income loss, while poultry farmers had to sell birds at half price. The dairy, poultry, and fish sub-sectors were particularly hard-hit. Despite government support, assistance primarily reached well-off farmers and larger businesses rather than smallholders. This study not only underscores lessons learned for Nepal in managing the pandemic and similar disasters but also offers insights for other countries in South Asia facing comparable constraints and opportunities. By investigating the pandemic’s repercussions and government interventions in Nepal, this research contributes to better preparedness and response strategies for future crises in livestock and agriculture. SAARC J. Agric., 21(2): 217-226 (2023)